Rancang Bangun Aplikasi Peringatan Dan Mitigasi Gempa Bumi Berbasis Mobile Hybrid - Ida Bagus Gede, Purwania; Sari Hartati, Rukmi; Divayana, Yoga (Majalah Ilmiah Teknologi Elektro, 2020)
BMKG and BNBP are organizations formed by the government to handle disasters both before, pre-disaster and after a disaster occurs. BMKG and BNBP have several early warning systems, but it requires a long and long process for information to reach the community. This research was conducted to produce applications that can provide warnings to the community when an earthquake occurs and can provide information on the nearest evacuation site. Also this application is designed to be able to connect with friends or close relatives when an earthquake disaster occurs. The application will send notifications automatically to friends or close relatives when the user is affected by an earthquake. This Earthquake Warning and Mitigation application was developed based on mobile hybrids by utilizing open source earthquake data from InaSAFE and integrated with the Google Maps API.